Morality and the Public Good in Post-Socialist European States - Sieben, Inge; Halman, Loek (Studies of Transition States and Societies, 2015)
In this study, we investigate morality in relation to the public good in post-socialist Europe. Public good morality is defined as the (non)acceptance of behaviour that contravenes the law and harms society and the greater good of the collective, such as cheating on taxes if one has the chance, paying cash to avoid taxes, not paying one’s fare in public transport, and claiming state benefits one is not entitled to. Using data from the European Values Study in 2008 on more than 30,000 respondents in 23 post-socialist states, we find that on average the level of public good morality is quite high: 8.4 on a ten-point scale. However, there are marked differences between individuals and between countries, which we attempt to explain by looking at the legacy of communist rule, processes of democratization and compliance attitudes. We find that individuals living in former Soviet states are more ‘lenient’ when it comes to actions that harm the collective. However, those who lived under communist rule for a longer time display higher (and not lower) levels of public good morality. The level of democracy in a country does not seem to add any explanatory power, but individuals who hold more democratic values appear to be morally less strict. Finally, compliance attitudes such as interpersonal trust and confidence in government do not seem to mediate the observed relationships between communist rule and democracy on the one hand and public good morality on the other hand.